Mucus Clearance Strategies in Mechanically Ventilated Patients - Ryan L. Goetz; Kadambari Vijaykumar; George M. Solomon; George M. Solomon (Frontiers in Physiology, 2022)
The use of airway clearance strategies as supplementary treatment in respiratory disease has been best investigated in patients with cystic fibrosis (CF) and non-cystic fibrosis bronchiectasis (NCFBE), conditions which are traditionally characterized by excessive mucus stasis and mucociliary dysfunction. A variety of airway clearance therapies both pharmacological and non-pharmacological have been shown to ameliorate disease progression in this population and have hence been assimilated into routine respiratory care. This self-propagating cycle of mucus retention and airway damage leading to chronic inflammation and infections can also be applied to patients with respiratory failure requiring mechanical ventilation. Furthermore, excessive trachea-bronchial secretions have been associated with extubation failure presenting an opportunity for intervention. Evidence for the use of adjunctive mucoactive agents and other therapies to facilitate secretion clearance in these patients are not well defined, and this subgroup still remains largely underrepresented in clinical trials. In this review, we discuss the role of mucus clearance techniques with a proven benefit in patients with CF and NCFBE, and their potential role in patients requiring mechanical ventilation while highlighting the need for standardization and adoption of mucus clearance strategies in these patient populations.